PREVENTIVE RISK MANAGEMENT STRATEGY FOR HYDROPONIC LETTUCE PRODUCTION AT CV SPIRIT WIRA UTAMA TANGERANG SELATAN BANTEN - Lilis Imamah Ichdayati; Muhamad Mahardika Abhirama; Armaeni Dwi Humaera; Zulmanery Zulmanery; Ahmad Mahbubi (Universitas Sebelas Maret, 2025)
Agribusiness companies face various risks during their production period, which can harm their operations. For instance, CV Spirit Wira Utama, a company engaged in lettuce production, experiences an average of 25% harvest loss due to unmarketable quality. Therefore, preventive measures are necessary to reduce the impact of risk losses. This study aims to identify and measure the risks associated with hydroponic lettuce crop production, map them, and develop preventive risk management strategies. The research design used primary data sources from CV Spirit Wira Utama in South Tangerang, Banten. Data collection involved observation, systematic interviews, and structured questionnaires. Risk measurement was carried out during the lettuce production process using hydroponic systems. The analysis tool used fishbone diagrams, house of risk (HOR), and Pareto diagrams. The results showed that there were 35 risk events and 41 risk agents in lettuce crop production. The preventive risk management strategy should be given to the highest risk measurement value, which is the water temperature in the nutrient toren exceeding 27 C. The risk mapping results obtained a total of 22 risk agents with an impact of 80%, making them a top priority for risk prevention strategies. There are 29 risk prevention strategies available to prevent future risk events. This study's results are vital as the combination of three analytical tools can detect in detail the risks that arise and their impact. This information can help mitigate these risks and serve as a basis for preparing production risk SOPs.